Trends and Determinants of Attitudes Towards People Living with HIV/AIDS Among Women of Reproductive Age in Tajikistan - Hakim Zainiddinov (University Library System, University of Pittsburgh, 2019)
Introduction: Despite having one of lowest rates of newly diagnosed HIV infections among former Soviet countries, Tajikistan has a substantial level of discriminatory attitudes towards people living with HIV/AIDS (PLWHA). While initial attempts were made to explore discriminatory attitudes of a wide range of professionals, women's general attitudes towards PLWHA received less scholarly attention. Employing a nationally representative sample from the 2000 and 2005 Multiple Indicator Cluster Surveys (MICS), sociodemographic determinants of HIV-related discriminatory attitudes of women aged 15-49 in Tajikistan were identified and examined over time. Methods:  A representative sample included 5,453 women of reproductive age from the capital city and four regions of Tajikistan. Two dichotomized scenarios  representing the agreement to let an HIV-infected teacher continue teaching in school and the willingness to buy food from an HIV-infected cashier were constructed. Univariate and multivariable analyses of HIV-related discriminatory attitudes were obtained using Stata 14. Results: Insignificant but positive changes were observed in the women's attitudes between 2000 and 2005. Logistic regression models showed that negative attitudes were associated with the lack of knowledge of HIV/AIDS prevention methods, endorsement of HIV/AIDS transmission misconceptions, and never having been tested for HIV (p≤0.001). Women living in the rural areas, married, with lower education, and from low income households were less tolerant towards PLWHA. Conclusions: The data from Tajikistan underscore the persistence of HIV-related discriminatory attitudes among low socioeconomic status women. The study findings can be potentially used to target the disadvantaged groups and guide the design and implementation of programs that promote voluntary HIV-testing, raise awareness about HIV/AIDS prevention methods, and help dispel transmission misconceptions.